ANALISIS RETORIKA KEADILAN DALAM TINDAK PIDANA KORUPSI DI INDONESIA STUDI KASUS GRATIFIKASI RAFAEL ALUN TRISAMBODO - Sandi, Maryam Priska Asmara; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study aims to analyze the rhetoric of justice in corruption cases in Indonesia, focusing on the case of gratification involving Rafael Alun Trisambodo. Through a qualitative approach using critical discourse analysis, this research explores how the concept of justice is represented in legal processes and public perceptions related to the case. Data were obtained from legal documents, media reports, and interviews with legal experts and academics. The analysis reveals a shift in the meaning of justice influenced by media narratives and political interventions, often blurring the lines between retributive and restorative justice. The study concludes that the rhetoric of justice in corruption cases in Indonesia tends to be used as a tool of legitimacy by certain actors, impacting inconsistent law enforcement and diminishing public trust. The implications of these findings provide a critical view of legal mechanisms and the need for reforms in the judicial system to ensure substantive justice for all parties.Keywords: rhetoric of justice, corruption, gratification, Rafael Alun Trisambodo, critical discourse analysis